2014
DOI: 10.5089/9781484385081.001
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Vulnerability in Developing Countries

Abstract: This paper examines how international remittances are affected by structural characteristics, macroeconomic conditions, and adverse shocks in both source and recipient economies. We exploit a novel, rich panel data set, covering bilateral remittances from 103 Italian provinces to 107 developing countries over the period 2005-2011. We find that remittances are negatively correlated with the business cycle in recipient countries, and increase in response to adverse exogenous shocks, such as natural disasters or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 57 publications
16
53
1
Order By: Relevance
“…The results in Table support the thesis that financial deepening in the migrant's home country favors the adoption of official transmission channels . On the other hand, and contrary to Bettin, Presbitero, and Spatafora (), the number of bank branches in Italy does not appear to play a role in determining the amount of remittances. This could depend on the fact that the banking channel is seldom used for remittance purposes (World Bank, ); moreover, this variable is also likely to be correlated with the level of regional economic activity, so its information content may be largely captured by income differential .…”
Section: Estimation and Resultsmentioning
confidence: 63%
“…The results in Table support the thesis that financial deepening in the migrant's home country favors the adoption of official transmission channels . On the other hand, and contrary to Bettin, Presbitero, and Spatafora (), the number of bank branches in Italy does not appear to play a role in determining the amount of remittances. This could depend on the fact that the banking channel is seldom used for remittance purposes (World Bank, ); moreover, this variable is also likely to be correlated with the level of regional economic activity, so its information content may be largely captured by income differential .…”
Section: Estimation and Resultsmentioning
confidence: 63%
“…As discussed in Bettin et al. (), the effect of financial development on remittances is ambiguous. A more efficient financial sector may encourage the receipt of remittances through lower transaction costs (Freund and Spatafora, ), or because a higher share of remittances will flow through formal channels.…”
Section: Resultsmentioning
confidence: 98%
“…However, as highlighted in Bettin et al. (), Giuliano and Ruiz‐Arranz () showed that remittances may compensate for reduced household access to credit in remittance‐receiving countries. In this case, remittances and financial development would be substitutes for each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Giuliano and Ruiz‐Arranz () find that remittances are typically pro‐cyclical for the remittance‐receiving country, while Frankel () and Bettin et al . () find that they are typically countercyclical.…”
mentioning
confidence: 99%